A critical analysis of civil society's engagement in South Africa's just energy transition: dynamics and debates - Ramasesane, Lerato (Graduate School of Development Policy and Practice, 2025)
South Africa is currently undergoing a Just Energy Transition (JET) that seeks to design and create a clean and just energy industry in South Africa. This process is underpinned by a rapid revision of energy sector policies, regulatory frameworks and debates around energy reform. The aim of the study is to critically analyse the debates and dynamics underpinning Civil Society Organisations' (CSOs) participation as key stakeholders in the JET process taking place within South Africa: How is civil society engaging in the energy reform process in general and specifically with regards to debates around JET in South Africa? Currently civil society engages in state-sanctioned and self-created platforms around JET, however the extent to which it participates, the challenges it faces, and the dynamics of this civil space are not well understood. The research is based on a qualitative research design and involved in-depth interviews with representatives from several CSOs involved in JET debates as well as desktop research. Strategic and purposive sampling was used as a method for choosing respondents best suited to provide answers for the research question. The research found that CSOs actively participate in energy transition debates in South Africa using a variety of strategies and tactics. These include litigation, public participation platforms, media, resistance campaigns and grassroots community activism. Whilst there have been considerable victories - including advocating for energy access, justice and broader consultation - CSOs face resource related challenges, threats and power dynamics whilst engaging in JET processes. There is also a disconnect between local and international CSOs working in this space. Recommendations are made for more funding and collaboration opportunities to increase the scope, depth and participation of civil society in the JET discourse. The research may assist policy makers, CSOs and researchers to better understand the current participation of civil society in the policymaking and reform process of energy transition in South Africa. Also, the debates and dynamics that characterise and inform their engagement.